First Report of Megafossils (Glossopteris Flora) From The Simlong Open Cast Mine, Rajmahal Basin, Jharkhand, India- Evidence for Coal Forming Vegetation in the Area - Joshi, Arun (Indian Forester, 2023)
The present investigation deals with the first report of the Glossopteris flora from the Barakar Formation of Simlong Open Cast Mine, Rajmahal Basin, Jharkhand, India. The assemblage is represented by pteridophytes and gymnosperms. Pteridophytes comprise Equisetalean axes whereas, gymnosperms include impressions of members of order Glossopteridales namely Glossopteri gigas, G. indica and Vertebraria indica. The present study is significant in widening the knowledge of the Glossopteris flora especially from the Simlong Open Cast Mine, Rajmahal Basin where the floral information is not known to now.